Kinetic studies of urban solid residues and leachate from sanitary landfill - de Almeida, Sonia [UNESP]; Lima, Evaneide N. [UNESP]; Crespi, Marisa Spirandeli [UNESP]; Ribeiro, Clovis Augusto [UNESP]; Schalch, Valdir (Springer, 2009)
Urban solid residues are constituted of food remaining, grass leaves, fruit peelings, paper, cardboard, rubber, plastic, etc. The organic fraction formed represents about 50% during the decomposition yields biogas and leachate, which are sources of pollution. Residue samples were collected from the landfill in different and cells from several ages and the corresponding leachate, both after treatments, were submitted to thermal analysis. Kinetic parameters were determined using Flynn-Wall-Ozawa method. The linear relation between the two kinetic parameters (ln A and E) was verified for organic residue urban's samples, but not for leachate's sample. The occurred difference can be attributed to the constituents present in leachate.
Keywords: Kinetic parameters; Landfill; Leachate